Changes In Learning Patterns During Covid-19 Pandemic: The Case Of Indonesian University Students - Sinta Novia (Journal of Arts and Education, 2023)
This study aimed at evaluating the learning process using e-learning and finding the changes in learning patterns in Indonesian university students’ during Covid-19 pandemic. Researcher has found out that students have changed their learning patterns during the Pandemic. Students who are initially accustomed to direct learning inevitably have to learn online to prevent transmission of the coronavirus. If we are aware of the positive side changing the learning paradigm in the era of the COVID-19 pandemic, it is more directed at efforts to improve the quality of teachers and students in the learning process.Keywords: Learning patterns, Covid-19 Pandemic.